OntoConnect: Domain-Agnostic Ontology Alignment using Graph Embedding with Negative Sampling - Chakraborty, Jaydeep; Sherif, Mohamed; Zahera, Hamada Mohamed Abdelsamee; Bansal, Srividya (Proceedings of the IEEE International Conference on Machine Learning and Applications)
Keywords: dice sherif hamada

Distinct photodynamics of κ-N and κ-C pseudoisomeric iron(ii) complexes - Dierks, Philipp; Kruse, Ayla; Bokareva, Olga S.; Al-Marri, Mohammed J.; Kalmbach, Jens; Baltrun, Marc; Neuba, Adam; Schoch, Roland; Hohloch, Stephan; Heinze, Katja; Seitz, Michael; Kühn, Oliver; et al. (Chemical Communications)
Two closely related FeII complexes with 2,6-bis(1-ethyl-1H-1,2,3-triazol-4yl)pyridine and 2,6-bis(1,2,3-triazol-5-ylidene)pyridine ligands are presented to gain new insights into the photophysics of bis(tridentate) iron(II) complexes. The [Fe(N^N^N)2]2+ pseudoisomer sensitizes singlet oxygen through a MC state with nanosecond lifetime after MLCT excitation, while the bis(tridentate) [Fe(C^N^C)2]2+ pseudoisomer possesses a similar 3MLCT lifetime as the tris(bidentate) [Fe(C^C)2(N^N)]2+ complexes with four mesoionic carbenes.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composite; Metallkomplexe; Optical and Magnetic Materials; Catalysis

Sprache in Politik und Gesellschaft. Perspektiven und Zugänge. Bericht von der 57. Jahrestagung des Leibniz-Instituts für Deutsche Sprache (als Online-Konferenz), 9. bis 11. März 2021 - Georgi, Christopher (Sprachreport)

Sprache in Politik und Gesellschaft. Perspektiven und Zugänge. Bericht von der 57. Jahrestagung des Leibniz-Instituts für Deutsche Sprache, 9. bis 11. März 2021 - Georgi, Christopher (Deutsche Sprache)

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England and several countries in Continental Europe we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance of maintaining good physical health in old age for cognitive functioning.
Keywords: Cognitive decline; health shocks; retirement; education; event study

The dynamic and heterogeneous effects of retirement on cognitive decline - Schmitz, Hendrik; Westphal, Matthias
We study effects of retirement on cognitive abilities (up to ten years after retirement) using data from 21 countries in Continental Europe, England, and the US, and exploiting early-retirement thresholds for identification. For this purpose, combines event-study estimations with the marginal treatment effect framework to allow for effect heterogeneity. This helps to decompose event-study estimates into true medium-run effects of retirement and effects driven by differential retirement preferences. Our results suggest considerable negative effects of retirement on cognitive abilities. We also detect substantial effect heterogeneity: Those who retire as early as possible are not affected while those who retire later exhibit negative effects.
Keywords: Cognitive abilities; retirement; event study; marginal treatment effects

Bestimmung von flussigkeitsseitigen Stoffübergangskoeffizienten für strukturierte Packungen basierend auf hydrodynamischen Analogien - Kämper, Marek

The Creation of Illegal Migration in the German Confederation, 1815–1866 - Schubert, Michael (Migrations and Border Processes. Practices and Politics of Belonging and Exclusion in Europe from the Nineteenth to the Twenty-First Century)

Arbeit und Melancholie - Vöing, Nerea

„Nicht alles lässt sich digital lösen“ – Jetzt schlägt die Stunde moderner Konzepte, meint Hochschuldidaktikerin Nerea Vöing - Vöing, Nerea (DUZ Magazin)

Besondere Formate der hochschuldidaktischen Weiterbildung. Stand der Praxis inklusive Good Practice-Beispiele - Vöing, Nerea; Franke, Kathrin; Sekyra, Anita (Handbuch Hochschuldidaktik)

»Ich bin froh darüber, dass das so passiert ist« - Kordts-Freudinger, Robert; Bücker, Diana; Schulte, Rebecca; Vöing, Nerea (Hochschule auf Abstand)

„Evidenz“, was meinen Sie damit? – Eine Interviewstudie zum Verständnis von Hochschullehrenden vom Evidenzbegriff - Vöing, Nerea; Leschke, Jonas; Daumiller, Martin (ZFHE)

Grenzen der Musik? Deutschsprachige Narrative zu Musik und Geräusch in den 1950er-Jahren - Tumat, Antje (Musikwissenschaft der Vielfalt. Festschrift Rebecca Grotjahn zum 60. Geburtstag)
Keywords: Neue Musik

Neue Wege in die Biologie: Verstehen mit Modellen - Originale – Theorien – Modellierung - Meister, Johannes; Trier, Ulrike; Upmeier zu Belzen, Annette

Attachment representation and emotion recognition ability in children with ADHD and their parents: A Study Protocol - Kissgen, R.; Franke, Sebastian; Krischer, M.; Susewind, M. (International Journal of Environmental Research and Public Health)

Zur inklusiven Betreuung von Kindern mit (drohender) Behinderung in Kindertageseinrichtungen in Bayern und im Rheinland. Ein Studienvergleich - Kißgen, R.; Wirts, C.; Limburg, D.; Wertfein, M.; Franke, Sebastian; Wölfl, J.; Austermühle, J. (Frühförderung interdisziplinär)

Attachment Representation and Emotion Recognition Ability in Children with ADHD and Their Parents: A Study Protocol - Kissgen, R.; Franke, Sebastian; Susewind, M.; Krischer, M. (International Journal of Environmental Research and Public Health)

Die Anfänge der Internationalen Ferienkurse für Neue Musik aus Gender-Perspektive - Tumat, Antje (Gender und Neue Musik)

Infant-Father Attachment in Infants Born Preterm. A Brief Report - Kissgen, R.; Franke, Sebastian; Jorjadze, N.; Roth, B.; Kribs, A. (International Journal of Developmental Science)

Exploring the paths towards service growth in manufacturing companies - Harrmann, L.; Böhm, Eva; Eggert, A. (2021 AMA Winter Academic Conference)

Ein kaiserlicher Wüterich und zwei antagonistische Simons. Der „Nero furens“ als Beispiel aus dem Paderborner Jesuitendramenkorpus - Elit, Stefan (NlatJb 23)

The Impact of Virtual Reality, Augmented Reality, and Interactive Whiteboards on the Attention Management in Secondary School STEM Teaching - Erofeeva, Maria; Klowait, Nils Oliver (2021 7th International Conference of the Immersive Learning Research Network (iLRN))

The Impact of Virtual Reality, Augmented Reality, and Interactive Whiteboards on the Attention Management in Secondary School STEM Teaching - Erofeeva, Maria; Klowait, Nils (2021 7th International Conference of the Immersive Learning Research Network (iLRN))

Hochschule auf Abstand
Trotz massiver Förderungen für die Digitalisierung ist die Präsenzlehre noch immer der Standard an deutschen Hochschulen. Aufgrund des Physical Distancing im Zuge der Corona-Pandemie musste sie jedoch kurzfristig fast vollständig digitalisiert werden. Die Beiträge des Bandes bieten einen multiperspektivischen Zugang zu den damit verbundenen Herausforderungen und beleuchten, wie die verschiedenen Akteur*innen die Umstellung auf digitale Lehr- und Lernformate umgesetzt und erlebt haben. Durch die Zusammenführung der verschiedenen Sichtweisen können die Bedarfe und Wünsche der einzelnen Akteursgruppen zusammengebracht und bei der nachhaltigen Weiterentwicklung der Hochschullehre besser berücksichtigt werden.

Engaging a product-focused sales force in solution selling: interplay of individual- and organizational-level conditions - Salonen, Anna; Terho, Harri; Böhm, Eva; Virtanen, Ari; Rajala, Risto (Journal of the Academy of Marketing Science)
Abstract This study explains how manufacturers tackle the critical managerial challenge of transforming a product-focused sales force to undertake solution selling. Through an application of configurational theory, the authors explain how individual and organizational conditions combine to determine salespeople’s engagement in solution selling. Multilevel, multisource data from the sales organization of a global supplier of building solutions represent input from salespeople ( N = 184), solution champions ( N = 23), and sales managers ( N = 26). A fuzzy set qualitative comparative analysis reveals no single, optimal way to overcome transformation challenges. Rather, consistent with prior research, solution selling requires certain types of salespeople, because value-based selling is a necessary condition for successful engagement. Beyond this foundational condition, a heterogeneous sales force can be engaged, as long as the organization provides appropriate support that is tailored to individual salespersons’ needs. The findings affirm that this viable support can come from either sales managers or solution champions.
Keywords: Marketing; Economics and Econometrics; Business and International Management

Online reviews generated through product testing: can more favorable reviews be enticed with free products? - Garnefeld, Ina; Krah, Tabea; Böhm, Eva; Gremler, Dwayne D. (Journal of the Academy of Marketing Science)
Abstract Online reviews have profound impacts on firm success in terms of sales volume and how much customers are willing to pay, yet firms remain highly dependent on customers’ voluntary contributions. A popular way to increase the number of online reviews is to use product testing programs, which offer participants free products in exchange for writing reviews. Firms that employ this practice generally hope to increase review quality and secure higher product rating scores. However, a qualitative study, experimental study, and multilevel analysis of a field study dataset of more than 200,000 online reviews by product testers combine to reveal that product testing programs do not necessarily generate higher quality reviews, nor better product ratings. Only in certain circumstances (e.g., higher priced products) does offering a product testing program generate these benefits for the firm. Therefore, companies should consider carefully if and when they want to offer product testing programs.
Keywords: Marketing; Economics and Econometrics; Business and International Management

Outcome-based contracting from the customers' perspective: A means-end chain analytical exploration - Schaefers, Tobias; Ruffer, Stefan; Böhm, Eva (Industrial Marketing Management)
Keywords: Marketing

Schreiben als Schlüsselkompetenz? - Scharlau, Ingrid; Haacke, Stefanie; Karsten, Andrea; Lahm, Swantje (Handbuch Hochschuldidaktik)

Untersuchung von Polymer-Dry-Blends und Bewertung ihrer Verarbeitungseigenschaften für den Lasersinterprozess (Studienarbeit) - Gawlikowicz, Roland

Wettkampfbezogene Emotionen im Sport – ein Scoping-Review - Wetzel, Änne; Güldenpenning, Iris; Weigelt, Matthias (German Journal of Exercise and Sport Research)
Zusammenfassung Jegliche Art von Emotionen im Sport spielen vor allem in Wettkampfsituationen eine bedeutende Rolle, wenn es darum geht, zu einem bestimmten Zeitpunkt die optimale Leistung abzurufen. Emotionen können Auswirkungen auf der physiologischen, perzeptuell-kognitiven oder behavioralen Ebenen haben. Daher bildet den Schwerpunkt des vorliegenden Scoping-Reviews, die Untersuchung der Bedeutung wettkampfbezogener (state) Emotionen von Sporttreibenden. Die Literaturrecherche ergab 1126 Arbeiten, aus denen 15 Studien die Einschlusskriterien erfüllten. Diese wurden hinsichtlich ihrer Themenschwerpunkte betrachtet: 1) Emotionen, Kognitionen und Angst; 2) Emotionen, Leistungsbeurteilung und Stress; 3) Emotionen und Leistungsziele; 4) Unterschiede emotionaler Ausprägung im Geschlecht und Leistungsniveau; 5) Einfluss von Kausalzuschreibungen auf die Emotionen. Anschließend wurden die in den vorgestellten Studien verwendeten emotionserfassenden Messinstrumente betrachtet und vorgestellt. Zusammengefasst erscheint die Erfassung wettkampfbezogener (state) Emotionen rund um das sportliche Geschehen (vor, während, danach) ein wesentlicher Bestandteil der angewandten Sportpsychologie, davon abgeleiteter Emotionsregulationsstrategien und somit der optimalen Leistungserbringung zu sein, auch wenn der (deutschsprachigen) sportpsychologischen Praxis bisher nur begrenzte validierte Messinstrumente vorliegen.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Examining the Perceptual-Cognitive Mechanism of Deceptive Actions in Sports - Polzien, Andrea; Güldenpenning, Iris; Weigelt, Matthias (Experimental Psychology)
Abstract. In several kinds of sports, deceptive actions are used to hinder the anticipation performance of an opponent. During a head fake in basketball, a player turns the head to one side but passes the ball to the other side. A pass with a head fake generates a head-fake effect in the observer, which is characterized by slower and more error-prone responses to the pass direction as compared to passes without a head fake. Whereas the head-fake effect has been replicated several times, the question of its origin with dynamic stimuli has not been answered yet. The present study includes four experiments, which are conducted to examine the perceptual-cognitive mechanism underlying the effect by using the model of dimensional overlap ( Kornblum et al., 1990 ) and the additive factors logic ( Sternberg, 1969 ). Results point to multiple processes contributing to the head-fake effect for dynamic stimuli, which operate not only at a perceptual level but also at a level of response selection.
Keywords: General Psychology; Arts and Humanities (miscellaneous); Experimental and Cognitive Psychology; General Medicine

A question of (perfect) timing: A preceding head turn increases the head-fake effect in basketball - Polzien, Andrea; Güldenpenning, Iris; Weigelt, Matthias (Plos one)

Electric and conventional vehicle usage in private and car sharing fleets in Germany - Habla, Wolfgang; Huwe, Vera; Kesternich, Martin (Transportation Research Part D: Transport and Environment)
Keywords: General Environmental Science; Transportation; Civil and Structural Engineering

Zustandsüberwachung zur Prognose der Restlebensdauer von Gummi-Metall-Elementen unter Berücksichtigung systembasierter Unsicherheiten - Bender, Amelie
Eine zustandsbasierte Instandhaltungsstrategie reduziert das Risiko eines Ausfalls eines technischen Systems bei gleichzeitig hoher Ausnutzung und planbaren Instandhaltungsmaßnahmen. Das Ziel dieser Arbeit liegt in der Entwicklung einer Zustandsüberwachung für Gummi-Metall-Elemente. Die Herausforderungen dieser Zustandsüberwachung leiten sich aus dem viskoelastischen Verhalten sowie dem komplexen Degradationsverhalten der Elemente ab. Infolge der daraus resultierenden Unsicherheiten werden die Elemente heutzutage präventiv instandgehalten. In Lebensdauerversuchen der Gummi-Metall-Elemente werden drei Messgrößen detektiert. Dabei wird mit der Temperatur eine Messgröße identifiziert, die am geeignetsten zur Beschreibung des Zustands der Elemente ist. Generell wird die Genauigkeit einer Zustandsüberwachung durch verschiedene Unsicherheiten beeinflusst. Für die Prognose der nutzbaren Restlebensdauer der Gummi-Metall-Elemente wird das Partikelfilter, eine verbreitete modellbasierte Methode zur Zustandsüberwachung technischer Systeme, weiterentwickelt, um Unsicherheiten im Verhalten und der Degradation der Elemente zu berücksichtigen. Anhand der Ergebnisse wird belegt, dass aufbauend auf dieser Zustandsüberwachung die Ausnutzung der Gummi-Metall-Elemente in realen Anwendungen durch eine präventive Instandhaltung erhöht werden kann. Damit bildet diese Arbeit die Basis für zukünftige, prädiktive Instandhaltungskonzepte für diese Elemente. Weiterhin bestätigt die Arbeit, dass eine Berücksichtigung vorliegender Unsicherheiten zu einem frühen Zeitpunkt im Entwicklungsprozess des Zustandsüberwachungssystems empfehlenswert ist.
Keywords: Zustandsüberwachung; Prognose der Restlebensdauer; modellbasierte Prognose; Partikelfilter; Unsicherheiten; Gummi; Verlässlichkeit; Lebensdauerversuche; Predictive Maintenance

FLight: FPGA Acceleration of Lightweight DNN Model Inference in Industrial Analytics - Ghasemzadeh Mohammadi, Hassan; Jentzsch, Felix; Kuschel, Maurice; Arshad, Rahil; Rautmare, Sneha; Manjunatha, Suraj; Platzner, Marco; Boschmann, Alexander; Schollbach, Dirk (Machine Learning and Principles and Practice of Knowledge Discovery in Databases)

Neural Correlates of Augmented Feedback Processing are Associated to Short-Term Behavioral Changes and Automaticity in Motor Learning - Krause, Daniel; Margraf, Linda; Weigelt, Matthias

Predictive value of valence-dependent neural correlates of augmented feedback processing for behavioral adaptation and learning in extensive motor learning - Krause, Daniel; Margraf, Linda; Weigelt, Matthias

Neural Processing of Augmented Feedback is Valence-Dependent and Changes After Extensive Practice of a New Motor Task - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Changes in valence-dependent neural correlates of augmented feedback processing after extensive motor sequence learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Effects of an Intervention for Promoting Basic Motor Competencies in Middle Childhood - Strotmeyer, Anne; Kehne, Miriam; Herrmann, Christian (International Journal of Environmental Research and Public Health)
The development of motor competencies is necessary for participation in the culture of sport, exercise, and physical activity, which in turn supports the development of a healthy lifestyle. A lack of physical activity in childhood and deficits in motor performance emphasize the relevance of interventions for promoting basic motor competencies. However, there are research desiderata with regard to such interventions. This article describes an intervention program for promoting basic motor competencies in middle childhood (around 6 to 10 years of age). The intervention was investigated in a longitudinal study from June 2019 to January 2020 (n = 200; 58% girls, M = 8.84 years, SD = 0.63) at three primary schools. The intervention was conducted once a week in physical education (PE). The comparison group participated in regular PE. The intervention showed significant effects on basic motor competencies in object movement but not in self-movement. The results demonstrate that positive effects on basic motor competencies can be achieved with the help of a relatively simple intervention. Further longitudinal studies are desirable as a means of substantiating the results and developing evidence-based concepts to support children in their development in the best possible way.
Keywords: Health; Toxicology and Mutagenesis; Public Health; Environmental and Occupational Health

Repeating head fakes in basketball: Temporal aspects affect the congruency-sequence effect - Polzien, A.; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 63rd Conference of Experimental Psychologists (TeaP))

Cognitive load reduces interference by head fakes in basketball - Güldenpenning, Iris; Kunde, W.; Weigelt, Matthias (Abstracts of the 63rd Conference of Experimental Psychologists (TeaP))

Der Einfluss von Kontextinformationen auf den Blicktäuschungseffekt im Basketball - Güldenpenning, Iris; Barkey, Thies; Jackson, Robin C.; Weigelt, Matthias (Talententwicklung und Coaching im Sport. Abstractband der 53. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

A multirate variational approach to Nonlinear MPC - Lishkova, Y.; Cannon, M.; Ober-Blöbaum, Sina

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (Microelectronics Reliability)
Ultrasonic wire bonding is a solid-state joining process, used in the electronics industry to form electrical connections, e.g. to connect electrical terminals within semiconductor modules. Many process parameters affect the bond strength, such like the bond normal force, ultrasonic power, wire material and bonding frequency. Today, process design, development, and optimization is most likely based on the knowledge of process engineers and is mainly performed by experimental testing. In this contribution, a newly developed simulation tool is presented, to reduce time and costs and efficiently determine optimized process parameter. Based on a co-simulation of MATLAB and ANSYS, the different physical phenomena of the wire bonding process are considered using finite element simulation for the complex plastic deformation of the wire and reduced order models for the transient dynamics of the transducer, wire, substrate and bond formation. The model parameters such as the coefficients of friction between bond tool and wire and between wire and substrate were determined for aluminium and copper wire in experiments with a test rig specially developed for the requirements of heavy wire bonding. To reduce simulation time, for the finite element simulation a restart analysis and high performance computing is utilized. Detailed analysis of the bond formation showed, that the normal pressure distribution in the contact between wire and substrate has high impact on bond formation and distribution of welded areas in the contact area.
Keywords: Ultrasonic heavy wire bonding; Co-simulation; ANSYS; MATLAB; Process optimization; Friction coefficient; Copper-copper; Aluminium-copper

Hybrid Prediction Method for Remaining Useful Lifetime Estimation Considering Uncertainties - Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
Predictive Maintenance as a desirable maintenance strategy in industrial applications relies on suitable condition monitoring solutions to reduce costs and risks of the monitored technical systems. In general, those solutions utilize model-based or data-driven methods to diagnose the current state or predict future states of monitored technical systems. However, both methods have their advantages and drawbacks. Combining both methods can improve uncertainty consideration and accuracy. Different combination approaches of those hybrid methods exist to exploit synergy effects. The choice of an appropriate approach depends on different requirements and the goal behind the selection of a hybrid approach. In this work, the hybrid approach for estimating remaining useful lifetime takes potential uncertainties into account. Therefore, a data-driven estimation of new measurements is integrated within a model-based method. To consider uncertainties within the system, a differentiation between different system behavior is realized throughout diverse states of degradation. The developed hybrid prediction approach bases on a particle filtering method combined with a machine learning method, to estimate the remaining useful lifetime of technical systems. Particle filtering as a Monte Carlo simulation technique is suitable to map and propagate uncertainties. Moreover, it is a state-of-the-art model-based method for predicting remaining useful lifetime of technical systems. To integrate uncertainties a multi-model particle filtering approach is employed. In general, resampling as a part of the particle filtering approach has the potential to lead to an accurate prediction. However, in the case where no future measurements are available, it may increase the uncertainty of the prediction. By estimating new measurements, those uncertainties are reduced within the data-driven part of the approach. Hence, both parts of the hybrid approach strive to account for and reduce uncertainties. Rubber-metal-elements are employed as a use-case to evaluate the developed approach. Rubber-metal-elements, which are used to isolate vibrations in various systems, such as railways, trucks and wind turbines, show various uncertainties in their behavior and their degradation. Those uncertainties are caused by diverse inner and outer factors, such as manufacturing influences and operating conditions. By expert knowledge the influences are described, analyzed and if possible reduced. However, the remaining uncertainties are considered within the hybrid prediction method. Relative temperature is the selected measurand to describe the element’s degradation. In lifetime tests, it is measured as the difference between the element’s temperature and the ambient temperature. Thereby, the influence of the ambient temperature on the element’s temperature is taken into account. Those elements show three typical states of degradation that are identified within the temperature measurements. Depending on the particular state of degradation a new measurement is estimated within the hybrid approach to reduce potential uncertainties. Finally, the performance of the developed hybrid method is compared to a model-based method for estimating the remaining useful lifetime of the same elements. Suitable performance indices are implemented to underline the differences between the results.
Keywords: Hybrid prediction method; Multi-model particle filtering; Uncertainty quantification; RUL estimation

On the applicability of time series features as health indicators for technical systems operating under varying conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (Proceedings of the Seventeenth International Conference on Condition Monitoring and Asset Management (CM 2021))
Several methods, including order analysis, wavelet analysis and empirical mode decomposition have been proposed and successfully employed for the health state estimation of technical systems operating under varying conditions. However, where information such as the speed of rotating machinery, component specifications or other domain-specific information is unavailable, such methods are often infeasible. Thus, this paper investigates the application of classical time-domain features, features from the medical field and novel features from the highly comparative time-series analysis (HCTSA) package, for the health state estimation of rotating machinery operating under varying conditions. Furthermore, several feature selection methods are investigated to identify features as viable health indicators for the diagnostics and prognostics of technical systems. As a case study, the presented methods are evaluated on real-world and experimentally acquired vibration data of bearings operating under varying speed. The results show that the selected features can successfully be employed as health indicators for technical systems operating under varying conditions.
Keywords: Wind turbine diagnostics; bearing diagnostics; non-stationary operating conditions; varying operating conditions; feature extraction; feature selection; fault detection; failure detection

Rule-based Diagnostics of a Production Line - Aimiyekagbon, Osarenren Kennedy; Muth, Lars; Wohlleben, Meike Claudia; Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
In the industry 4.0 era, there is a growing need to transform unstructured data acquired by a multitude of sources into information and subsequently into knowledge to improve the quality of manufactured products, to boost production, for predictive maintenance, etc. Data-driven approaches, such as machine learning techniques, are typically employed to model the underlying relationship from data. However, an increase in model accuracy with state-of-the-art methods, such as deep convolutional neural networks, results in less interpretability and transparency. Due to the ease of implementation, interpretation and transparency to both domain experts and non-experts, a rule-based method is proposed in this paper, for prognostics and health management (PHM) and specifically for diagnostics. The proposed method utilizes the most relevant sensor signals acquired via feature extraction and selection techniques and expert knowledge. As a case study, the presented method is evaluated on data from a real-world quality control set-up provided by the European prognostics and health management society (PHME) at the conference’s 2021 data challenge. With the proposed method, our team took the third place, capable of successfully diagnosing different fault modes, irrespective of varying conditions.
Keywords: PHME 2021; Feature Selection Classification; Feature Selection Clustering; Interpretable Model; Transparent Model; Industry 4.0; Real-World Diagnostics; Quality Control; Predictive Maintenance

Anomaly detection in hot forming processes using hybrid modeling - Lenz, Cederic; Henke, Christian; Trächtler, Ansgar (2021 26th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))